Henry IV, part 1. - Shakespeare; Burrell, John, 1910-1972.; Copley, Peter, 1915-2008.; Parks, Gower; Menges, Herbert, 1902-1972.; Shakespeare, William, 1564-1616.; Old Vic Company; Theatre Incorporated (Organization : New York, N.Y.); New Century Theatre (Organization : New York, N.Y.); Richard L. Coe Theater Programs Collection (Library of Congress) (1946)
New Century Theatre, Trebuhs Realty Co., Inc., The Old Vic Theatre Company presents "Henry IV, Part 1," by William Shakespeare, staged by John Burrell, music by Herbert Menges, costumes by Roger Furse, scenery by Gower Parks, lighting by John Sullivan, fights arranged by Peter Copley, orchestra under the direction of Herbert Menges.
New Century Theatre, week beginning Monday, June 10, 1946. June 12-13.
Title devised by Library staff.
Cast: Nicholas Hannen, Michael Warre, Robin Lloyd, Peter Copley, Kenneth Edwards, Cecil Winter, George Relph, Miles Malleson, Laurence Olivier, David Kentish, Harry Andrews, William Monk, Frank Duncan, Ralph Richardson, Michael Raghan, Sidney Tafler, George Rose, Ena Burrill, Margaret Leighton, Diana Maddox, Joseph James, Frank Duncan, William Squire, John Garley, Kenneth Edwards, Lawrence Carr, George Cooper, Carl James, John Reilly, Sandy Roe.
LC copy shelved under: Henry IV.
With: Henry IV, Part II / William Shakespeare -- Uncle Vanya / Anton Chekhov -- Oedipus / Sophocles -- The Critic / Richard Brinsley Sheridan. Issued together.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- New York (State) -- New York; Playbills -- New York (State) -- New York; Theater programs -- 1946.; Playbills -- 1946.